2014
DOI: 10.2500/ajra.2014.28.4044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Inferior Turbinoplasty with the use of CO2Laser, Radiofrequency, and Electrocautery

Abstract: The CO2 laser, radiofrequency and electrocautery offer excellent postoperative results in turbinoplasty cases under local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
6
13
0
1
Order By: Relevance
“…4 Many clinical studies demonstrated that RF turbinate surgery is effective and safe. 16,17,20,22,[25][26][27] Energy from RF causes fibrosis of the underlying stroma, while leaving the surface epithelium intact. In agreement with our results, Rhee et al 25 found that STT and ciliary beat frequency were preserved after RF turbinate surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 Many clinical studies demonstrated that RF turbinate surgery is effective and safe. 16,17,20,22,[25][26][27] Energy from RF causes fibrosis of the underlying stroma, while leaving the surface epithelium intact. In agreement with our results, Rhee et al 25 found that STT and ciliary beat frequency were preserved after RF turbinate surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the impossibility of using a fiber, the access towards the tail of the inferior nasal turbinate is hampered, the effectiveness of the therapy being thus low in the respective area. Numerous studies in the literature highlight medium and long-term effectiveness of the volumetric reduction of the inferior nasal turbinates mucosa with the CO2 laser 77,78 .…”
Section: Monosymptomatic Nasal Obstruction Without Septal Deviationmentioning
confidence: 99%
“…Prokopakis et al [18] compared the use of CO 2 laser with radiofrequency and electrocautery to evaluate their outcome and effect on nasal obstruction using subjective visual analogue scale and objective rhinomanometry. The study found 86% of patients in the CO 2 laser group reported subjective improvement in nasal obstruction, but no statistical difference was found among these three groups.…”
Section: Laser Turbinectomymentioning
confidence: 99%